2021
DOI: 10.1155/2021/3995789
|View full text |Cite
|
Sign up to set email alerts
|

The Role of PSA Density among PI-RADS v2.1 Categories to Avoid an Unnecessary Transition Zone Biopsy in Patients with PSA 4-20 ng/mL

Abstract: Objective. To evaluate the role of prostate-specific antigen density (PSAD) in different Prostate Imaging Reporting and Data System version 2.1 (PI-RADS v2.1) categories to avoid an unnecessary biopsy in transition zone (TZ) patients with PSA ranging from 4 to 20 ng/mL. Materials and Methods. In this retrospective and single-center study, 333 biopsy-naïve patients with TZ lesions who underwent biparametric magnetic resonance imaging (bp-MRI) were analyzed from January 2016 to March 2020. Multivariate logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…Some previous studies have used PI-RADS for PCa screening [ 26 , 27 ]. Wang et al [ 26 ] showed that for TZ patients with PSA levels of 4–20 ng/mL, the PI-RADS V2.1 score detected PCA with an AUC of 0.889.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some previous studies have used PI-RADS for PCa screening [ 26 , 27 ]. Wang et al [ 26 ] showed that for TZ patients with PSA levels of 4–20 ng/mL, the PI-RADS V2.1 score detected PCA with an AUC of 0.889.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies have used PI-RADS for PCa screening [ 26 , 27 ]. Wang et al [ 26 ] showed that for TZ patients with PSA levels of 4–20 ng/mL, the PI-RADS V2.1 score detected PCA with an AUC of 0.889. Sun et al [ 27 ] incorporated risk factors, including the PSA level and PI-RADS V2 score into a nomogram, which showed better PCa prediction performance (AUC = 0.876) than PI-RADS V2 only.…”
Section: Discussionmentioning
confidence: 99%
“…We selected different thresholds of mPSAD to obtain similar performance in our series of PI-RADS 3 than that of Görtz et al [22,81]. The use of appropriate thresholds in different populations has been previously described for mPSAD [19][20][21][82][83][84][85][86][87][88][89][90][91][92][93][94][95].…”
Section: Discussionmentioning
confidence: 99%
“…For example, no significant difference in PCa detection rates has been reported for PSA between 4 ng/mL and 10 ng/mL (11.8%–20.5%) and 10–20 ng/mL (20.5%–25.0%). Therefore, a study by Wang et al 56 included patients with PSA within 4–20 ng/mL. Second, differences in the clinically significant predictors across studies lead to diversity in model building.…”
Section: Discussionmentioning
confidence: 99%